Studi Penyusutan dan Konsolidasi Tanggul Banjir Tanah Rawa (Studi Kasus Di DAS Tulang Bawang) - Rini, Sri Nawang (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2019)
Flood dyke as construction made of soil, will usually experience a settlement, thus studies are needed to determine the shrinkage and settlement behavior that occurs in swamp flood dyke in the Tulang Bawang River Basin, by laboratory research and field observation. By USCS Method, we’ve gotten samples as sandy clay (SC) soil type and samples of high clay plasticity (CH), while by USDA Method, we’ve gotten all samples of claysoil type. Physically, the soil has a high degree of saturation and porosity and refers to soil properties such as volume weight, void ratio, mass density and water content, so the soil tends to be a clay soil with less organic where the clay content is known to range between 36, 44% - 79,94%, and organic content ranged from 11,38% - 22,43%. The average percentage of total settlement at flood dyke was most dominant du to linear shrinkage which contributed 42,51%, followed by soil consolidation under the dyke of 34,48%, subsequently caused by a settlement immediately and dyke consolidation, respectively 18,32% and 4,62%. The settlement due to consolidation occurs slowly such the process of void ratio discharge due to loading, different to the settlement due to linear shrinkage and the immediate settlement that is considered to occur immediately (because there is still very least research on the timing of this settlement). The value of settlement relation to time in the downstream and upstream river areas reviewed will be different, where the settlement in the downstream area will give a higher value than in the upstream, which is dependent on the depth of the soft soil.